Kajian Pertumbuhan Dan Produksi Varietas Jagung Lokal Dan Kacang Hijau Dalam Sistem Tumpangsari - Febby Polnaya; J.E Patty (Agrologia, 2012)
The objective of  this research was to determine appropriate variety combinations maize and mungbeans in multiple cropping system and the effect on yield, and also to determine Land Equivalency Ratio in the multiple cropping system. The experiment was conducted in Paso Village, Ambon City. A Randomized Block Design was used with two factors The first factor was maize variety consisting of 3 varieties: BISI-2 hybrid (J1), local variety with purple seeds (J2) and local variety with white seeds (J3). The second factor was mungbean variety, consisting of 3 varieties:  Murai variety (K1), local variety with red seeds (J2) and local variety with matt seeds (J3). Each treatment had three replicates and 6 monocultures were added as control.  Results of the experiment showed that maize variety and mungbeans variety affected significantly on growth and crop yield.  BISI-2 maize produced  highest seed number per row, 100 seed weight and seed weight per plot, and pod number per plant.  J1K1 treatment combination gave highest seed weight per hectare, i.e. 7,63 ton of maize and  0.73 ton/ha of mungbean seeds.  There was a significant effect of the interaction on Land Equivalency Ratio, and the highest value (4.07) was found in the treatment combination of J1K1